Higher Reflective and Spiritual Capacities as Principle of Interpersonal Perception and Communication - G V Ozhiganova (Peoples' Friendship University of Russia (RUDN University), 2012)
In this article reflexive and spiritual capacities are reviewed; their definition is suggested; their interrelation and important role in the process of interpersonal perception and communication are stated. The systematization and generalization of modern research dedicated to this topic are carried out.